Influence of Out Patient Registration Services on Patient Satisfaction in F.L. Tobing Hospital City of Sibolga In 2021 - A Cross-Sectional Study of Tertiary Hospitals in Sibolga - Benri Situmorang (Science Midwifery, 2022)
This paper is to examine the quality and satisfaction of walking patients at the Sibolga City Hospital. The outpatient satisfaction was analyzed when the patient was registered at the hospital. This study intends to measure the quality of service on the basis of satisfaction by measuring the level of patient satisfaction when receiving services at the registration stage at the hospital. One of the principles of quality health services is service that can satisfy everyone for the services received in accordance with the standards of the professional code of ethics that have been set by the government. This study aims to determine the effect of outpatient registration services on patient satisfaction at the F.L. General Hospital Tobing City of Sibolga in 2021. This type of research is a quantitative research with a cross sectional approach. The population in this study were all outpatients who came for treatment at the time of the study, the number of patients seeking treatment per day was 450 people at the F.L.Tobing Hospital, Sibolga City in 2021 and a sample of 45 people. Methods of data analysis by means of univariate analysis and bivariate analysis.